Kepuasan Pasien pada Telefarmasi vs Farmasi Konvensional: Analisis SERVQUAL - Lusy Noviani; Dion Notario; Wanda Aurina (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Telepharmacy offers a promising solution to overcome the geographical limitations of traditional pharmacies. However, concerns regarding the quality of services delivered through telepharmacy highlight the need for a comprehensive evaluation of patient satisfaction. This study aimed to compare patient satisfaction between telepharmacy and conventional pharmacy services and to identify areas for improvement. A cross-sectional study was conducted in March and April 2024, involving a sample of 136 customers from the Atma Jaya Teaching Pharmacy in North Jakarta. Patient satisfaction was measured using a validated questionnaire, and key satisfaction dimensions were identified through Importance-Performance Analysis (IPA). The analysis revealed that both telepharmacy and conventional pharmacy services demonstrated strengths in the dimensions of Assurance and Responsiveness, which are critical to customer satisfaction (quadrant II : keep up the good work). Meanwhile, Reliability and Empathy were perceived as less important in both service models (quadrant III : low priority). The Tangible dimension, however, was identified as an area requiring improvement (quadrant I : concentrate here). These findings suggest that telepharmacy can provide patient satisfaction comparable to conventional pharmacies, particularly in the dimensions of Assurance and Responsiveness. However, the Tangible dimension remains a key area for improvement.